2012
DOI: 10.3109/02713683.2012.707269
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Induced Changes in Corneal Viscoelastic Properties After 23-Gauge Pars Plana Vitrectomy Using Ocular Response Analyzer

Abstract: Corneal viscoelastic properties are not significantly influenced in the late postoperative period by 23-G TSV which is a minimal invasive vitreoretinal surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…Here, analysis of eyes that had prior laser or surgical procedures was limited to those who had undergone such procedures >3 months before enrollment. A growing body of evidence shows that for eyes that have undergone phacoemulsification, there are no residual effects on corneal biomechanical parameters beyond the 3-month postoperative period [30][31][32][33]. Similarly, in line with the data shown in our study, Hassan et al 41 demonstrate that after 3 months, Corvis measurements including highest concavity time return to baseline.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Here, analysis of eyes that had prior laser or surgical procedures was limited to those who had undergone such procedures >3 months before enrollment. A growing body of evidence shows that for eyes that have undergone phacoemulsification, there are no residual effects on corneal biomechanical parameters beyond the 3-month postoperative period [30][31][32][33]. Similarly, in line with the data shown in our study, Hassan et al 41 demonstrate that after 3 months, Corvis measurements including highest concavity time return to baseline.…”
supporting
confidence: 94%
“…Prior studies have demonstrated that there are no detectable changes in corneal biomechanical parameters as a result of intraocular surgery, including phacoemulsification, beyond the 3-month postoperative period. [30][31][32][33] All outputs were reviewed to ensure that films were not interrupted by eyelid movements, and readings were not disrupted by eyelash impact on the corneal surface. Corvis measurements were obtained in duplicates and results were averaged, to minimize effects of test-retest variability noted in prior studies.…”
Section: Subjectsmentioning
confidence: 99%
“…; Seymenoğlu et al. ). Corneal hysteresis significantly reduced after clear corneal cataract surgery, and it was returned preoperative level approximately 14 days later in a study (Kandarakis et al.…”
Section: Discussionmentioning
confidence: 97%
“…Some biomechanical changes have been reported after scleral procedures, but such a relationship has not been investigated for strabismus surgery before (17). Two studies have investigated the effects of scleral procedures on corneal biome-chanical properties before Seymenoğlu et al (18) who evaluated 23-gauge transconjunctival sutureless vitrectomy (23-G TSV) and Ruiz-De-Gopegui et al (19) who investigated the effects of encircling scleral buckle (SB).…”
Section: Discussionmentioning
confidence: 99%